The Impact Of Guidance And Counseling On Students’ Psychosocial Development - Alya Fatini; Mahdi NK; Syaiful Indra (Journal of Innovative and Creativity, 2025)
Adolescence is a developmental stage characterized by various emotional, cognitive, and social changes that may affect individuals’ psychosocial well-being. In the context of secondary education, particularly in Vocational High Schools (Sekolah Menengah Kejuruan/SMK), adolescents face academic demands, social relationships, and identity formation processes that may lead to psychosocial problems if not properly managed. Therefore, the presence of guidance and counseling services in schools plays an important role in supporting students’ psychosocial development in an optimal manner. This study aimed to identify psychosocial problems experienced by students at SMK Gandapura, Bireuen Regency, to examine the implementation process of Islamic guidance and counseling services at the school, and to analyze the impact of Islamic guidance and counseling on adolescents’ psychosocial development. This research employed a qualitative approach, with data collected through written interviews using open-ended questionnaires. The research participants consisted of 32 students of SMK Gandapura who had participated in guidance and counseling services. The findings indicate that adolescents’ psychosocial conditions involve an interaction between emotional and cognitive aspects with the social environment and interpersonal relationships. In the domains of emotion and cognition within the school environment, students experienced emotional pressure, anxiety, discomfort, and confusion that affected learning processes and social interactions. However, support provided by guidance and counseling teachers and peers played an important role in reducing the negative effects of emotional distress and enhancing students’ psychosocial adaptation. Students also reported positive changes after participating in counseling services, such as feeling calmer, relieved, and better understood. Overall, Islamic guidance and counseling at SMK Gandapura functions as a responsive support system and contributes positively to students’ psychosocial development.